Biogas enhancement in the anaerobic digestion of thermo-chemically pretreated sludge by stimulating direct interspecies electron transfer by biochar and graphene - Almegbl, Abdulaziz Mohammed; Munshi, Faris Mohammad A.; Khursheed, Anwar (Frontiers in Chemical Engineering, 2024)
Pretreatment of waste-activated sludge (WAS) to disintegrate the sludge matrix and amendment of its AD with carbon-based materials (CMs) to accelerate direct interspecies electron transfer (DIET) is necessary to achieve the maximum biogas potential of the abundant and habitat-threatening organic waste (WAS). Anaerobic digestion (AD) of WAS pretreated thermo-chemically at 0.5% NaOH (g/g dry sludge) and 125 °C microwave irradiation was amended by biochar doses of 0-40 g/L and graphene doses of 50-1000 mg/L in batch operation mode. Hybrid pretreatment of WAS deteriorated dewaterability but solubilized 38% of total chemical oxygen demand (COD). AD amended with 10 g/L biochar and 100 mg/L graphene had the optimum accumulative methane yield of 183.6 and 153.8 mL/gVS, respectively, which correspond to 42.8 and 24.8% increase compared to un-amended control assay with maximum methane content of 70.3% and 71.9%, respectively. Digestate of biochar-and graphene-amended assays resulted in higher TS% and alkalinity, reduced sCOD, VFA, and turbidity, and increased particle size distribution compared to control. Biochar-amended digestate had improved dewaterability, while digestate of grapheneamended assays resulted in inferior dewaterability compared to control. The t-test showed a significant difference between the biochar and graphene amended batch assays, while principal component analysis (PCA) indicated that biogas yield was closely correlated with the pH.CMs-amended batch assays demonstrated superb fitting with modified Gompertz, logistic, and first-order models with a coefficient of determination above 0.97. Microbial community abundance and diversity were affected by CMs amendment, resulting in increased acetoclastic methanogen growth and transformation of the methanogenic metabolic pathways. Extended pilot scale study and techno-economic and life cycle assessments are required to investigate the environmental impacts and feasibility.